Severe graft‐versus‐host disease‐like enterocolitis accompanied with cytomegalovirus‐reactivation in drug‐induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms. Issue 8 (2nd May 2022) - Takamiyagi, Saeko; Iriki, Hisato; Asahina, Yasuhiko; Furuichi, Yuki; Funakoshi, Takeru; Ichikawa, Masataka; Mikami, Yohei; Okita, Hajime; Sakiyama, Tomo; Inazumi, Toyoko; Amagai, Masayuki; Takahashi, Hayato
Abstract: Drug‐induced hypersensitivity syndrome (DIHS)/drug reaction with eosinophilia and systemic symptoms (DRESS) is a severe drug adverse reaction with skin eruption and visceral organ involvement. The characteristic clinical features of DIHS/DRESS are reactivation of human herpesviruses (HHV) and the development of autoimmune diseases, but their pathogenesis and associations are not yet understood. Here, we report a 66‐year‐old man who presented with fever, generalized erythema, diffuse lymphadenopathy, and diarrhea after 3 weeks of treatment with zonisamide. Reactivation of HHV‐6 and cytomegalovirus (CMV) was detected during the clinical course. The patient was diagnosed with DIHS/DRESS and treated with systemic prednisolone, i.v. immunoglobulin therapy, and ganciclovir. However, severe enterocolitis persisted for 6 months. A series of examinations revealed features of both CMV enterocolitis, as indicated by identification of a few CMV‐positive cells on immunohistochemical analysis, and graft‐versus‐host disease (GVHD)‐like enterocolitis indicated by orange‐peel appearance on endoscopic examination and histopathological loss of goblet cells. Intractable enterocolitis continued and the patient finally died of pneumonia. An autoimmune predisposition in DIHS/DRESS patients in combination with CMV reactivation was considered to trigger the severe enterocolitis of this case that showed GVHD‐like features of the gastrointestinal tract. GVHD‐like organ damage is a pathological condition rarely observed in DIHS/DRESS but should be recognized as one of the most severe complications of the disease.